Knowledge about transsexuality among a nursing team in a teaching clinic in the city of São Paulo - Souza, Rafael Luiz de; Silva, Gabriela Sousa da; Terra, Maria Fernanda; Terrazas, Caroline (O Mundo da Saúde, 2025)
This article aims to identify the knowledge of the nursing team in a Teaching Clinic regarding the trans population. It is a qualitative and descriptive study conducted with 10 nursing professionals from this Teaching Clinic located in the city of São Paulo. Data were collected in June 2023 through in-person interviews, consisting of both closed and open-ended questions, which were transcribed and analyzed using the Collective Subject Discourse technique. The empirical material was analyzed and grouped into six key expressions: Transgender Identity; Transition; Appearance and Respect; Nursing Care; Lack of Preparation. It was identified that, although there is an understanding of the health needs of this population, difficulties persist in implementing care practices that respect gender-specific needs. The study highlights the importance of integrating the topic of transsexuality into training curricula and continuing education spaces to ensure more inclusive and equitable healthcare services.